Rumah Yeop Abdul Jalil, Kampung Padang Tenggala, Bota Kanan, Perak - Chang, Eric; Zulkifli Yasin; Lim, Choong Kian; Tuty Mazura Mashhor; Lim, Khim Guan; Mohd. Arif Oh; Elina Mohd. Husini; Mohd. Hafizal Mansor (Skudai : Universiti Teknologi Malaysia, 1997)
Kajian Lukisan Terukur (Jabatan Senibina) - Universiti teknologi Malaysia, 1997